Innovation of Automatic Anti-Freezing Batik Wax Filtering Technology for the Revitalization of Sustainable Batik Entrepreneurship Based on Intellectual Property IDD000075738 - Widiana, Muslichah Erma; Adityo, R Dimas; Fahruddin, A’rasy; Sugianto, Herman (Sebatik, 2025)
Traditional batik enterprises in Indonesia face major challenges in sustaining productivity, efficiency, and global competitiveness. One key issue is the manual filtering of batik wax (malam), which often causes clogging and solidification, disrupting production and reducing batik quality. This research introduces an Automatic Anti-Clog Batik Wax Filtering Technology as an innovative solution for revitalizing sustainable batik entrepreneurship, registered under Industrial Design Intellectual Property IDD000075738. The study aims to develop a practical technology that automatically filters batik wax, maintains an ideal temperature, and prevents freezing during the production process. This innovation is expected to improve production efficiency, maintain motif quality, and enhance the resilience of small and micro batik enterprises. The research adopts a Research and Development (R&D) approach through applied experimentation, engineering design, and co-creation with local batik artisans. The two-year project includes wax characterization, temperature analysis, prototype design, and field testing with Keyna Gallery, a natural dye batik producer in Jombang. The outcomes include a simple patent, a functional prototype, and international journal publications. With a targeted Technology Readiness Level (TRL) of 7–9, this innovation supports SDG 8 (Decent Work and Economic Growth) and SDG 12 (Responsible Consumption and Production), promoting a sustainable, efficient, and globally competitive batik industry.